Wealth and subjective well-being in Germany - Antje Jantsch; Julia Le Blanc; Tobias Schmidt (Deutsche Bundesbank, 2022)
Wealth in addition to income determines to a large degree an individual's consumption opportunities and economic situation, which should in turn affect their subjective well-being. We analyse empirically the relationship between life satisfaction as an indicator of subjective well being and households' wealth. We contribute to the scarce literature on wealth and well-being using micro-data from the German wealth survey, Panel on Household Finances - PHF, for 2010 and 2014. Using panel regression models, we find that (i) individuals' life satisfaction is statistically significant and positively associated with their households' wealth holdings, (ii) different components of wealth, such as real and financial assets, as well as debt, have differential effects on life satisfaction, (iii) both wealth levels and wealth holdings relative to other households matter for life satisfaction. Our study shows that it is important to consider wealth, in addition to income, when analysing individuals' life satisfaction.
Keywords: I31; D19; D31; 330; wealth; debt; assets; life satisfaction; relative wealth; subjective well-being